The Influence of Organizational Justice and Social Support on Employee Performance at PT Han Young Indonesia, Majalengka Regency - Fikri Firmansyah; Agi Syarif Hidayat (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to analyze the influence of organizational justice and social support on employee performance at PT Han Young Indonesia in Majalengka Regency. The main issue addressed in this study is the suboptimal employee performance, which is suspected to be influenced by perceptions of organizational justice and the level of social support in the workplace. The study employs a quantitative approach with a causal design. The sample consists of 171 respondents selected from a population of 300 permanent employees using the Slovin formula with a 5% margin of error. Data were collected via a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS 25. Indicates a relatively small contribution. This study concludes that social support is a more consistent factor in improving performance and provides a theoretical contribution to the development of the Job Demands–Resources model as well as practical implications for more supportive human resource policies.